Atrial fibrillation and risk of incident heart failure with reduced versus preserved ejection fraction. Issue 5 (24th May 2021) - Nicoli, Charles D; O'Neal, Wesley T; Levitan, Emily B; Singleton, Matthew J; Judd, Suzanne E; Howard, George; Safford, Monika M; Soliman, Elsayed Z
Abstract : Objective: Associations between atrial fibrillation (AF) and heart failure (HF) have been established. We compared the extent to which AF is associated with each primary subtype of HF, with reduced (HFrEF) versus preserved ejection fraction (HFpEF). Methods: We included 25 787 participants free of baseline HF from the REGARDS (REasons for Geographic And Racial Differences in Stroke) cohort. Baseline AF was ascertained from ECG and self-reported history of physician diagnosis. Incident HF events were determined from physician-adjudicated review of hospitalisation medical records and HF deaths. Based on left ventricular ejection fraction (LVEF) at the time of HF event, HFrEF, HFpEF, and mid-range HF were defined as LVEF <40%, ≥50% and 40%–49%, respectively. Multivariable Cox proportional-hazards models examined the association between AF and HF. The Lunn-McNeil method was used to compare associations of AF with incident HFrEF versus HFpEF. Results: Over a median of 9 years of follow-up, 1109 HF events occurred (356 HFpEF, 388 HFrEF, 77 mid-range and 288 unclassified). In a model adjusted for sociodemographics, cardiovascular risk factors, and incident coronary heart disease, AF was associated with increased risk of all HF events (HR 1.67, 95% CI 1.38 to 2.01). The associations of AF with HFrEF versus HFpEF events did not differ significantly (HR 1.87 (95% CI 1.38 to 2.54) and HR 1.65 (95% CI 1.20 to 2.28), respectively; p value for difference=0.581). These associations were consistent in sex and race subgroups. Conclusions: AF is associated with both HFrEF and HFpEF events, with no significant difference in the strength of association among these subtypes.